2022
DOI: 10.3389/fvets.2022.919077
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and immortalization of macrophages derived from fetal porcine small intestine and their susceptibility to porcine viral pathogen infections

Abstract: Macrophages are a heterogeneous population of cells that are present in all vertebrate tissues. They play a key role in the innate immune system, and thus, in vitro cultures of macrophages provide a valuable model for exploring their tissue-specific functions and interactions with pathogens. Porcine macrophage cultures are often used for the identification and characterization of porcine viral pathogens. Recently, we have developed a simple and efficient method for isolating primary macrophages from the kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…ASFV is a highly pathogenic virus with a marked tropism for cells of the monocyte-macrophage lineage (21). Similar to the IPKM and IPIM cell lines reported in our recent studies (6,10), IPLuM were confirmed to be susceptible to ASFV infection and to facilitate the propagation of the virus very efficiently. It has been reported that the titers of replicating ASFV isolates were much lower in IPAM than in primary PAM (22).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…ASFV is a highly pathogenic virus with a marked tropism for cells of the monocyte-macrophage lineage (21). Similar to the IPKM and IPIM cell lines reported in our recent studies (6,10), IPLuM were confirmed to be susceptible to ASFV infection and to facilitate the propagation of the virus very efficiently. It has been reported that the titers of replicating ASFV isolates were much lower in IPAM than in primary PAM (22).…”
Section: Discussionsupporting
confidence: 83%
“…At each passage, the cells were detached using TrypLE express solution (Thermo Fisher Scientific, Waltham, MA), and the number of harvested cells was measured using a Bio-Rad TC20 automated cell counter. Immortalized porcine intestinal macrophages (IPIM) and immortalized porcine kidney-derived macrophages (IPKM), which are highly sensitive to the field ASFV isolates and celladapted ASFV isolate reported in our recent studies (6,10), were also passaged in the same way.…”
Section: Establishment Of Iplum and Subculturing Of Immortalized Cellsmentioning
confidence: 99%
“…Similarly, Takenouchi et al established an immortalized cell line by transferring the SV40 large T antigen and porcine TERT genes into primary porcine kidney-derived macrophages using lentiviral vectors [ 287 ]. Using the same approach, these authors also successfully immortalized macrophages from lung and small intestine [ 288 , 289 ]. These cells retain many features of primary macrophages and are susceptible to infection by ASFV or PRRSV and may represent useful tools for studying the interaction of these porcine pathogens with macrophages [ 288 , 290 , 291 ].…”
Section: Porcine Macrophage Cell Linesmentioning
confidence: 99%
“…Using the same approach, these authors also successfully immortalized macrophages from lung and small intestine [ 288 , 289 ]. These cells retain many features of primary macrophages and are susceptible to infection by ASFV or PRRSV and may represent useful tools for studying the interaction of these porcine pathogens with macrophages [ 288 , 290 , 291 ].…”
Section: Porcine Macrophage Cell Linesmentioning
confidence: 99%
“…To propagate blood‐derived macrophages (BMs) using such a mixed culture system, it is first necessary to identify appropriate feeder cells that can be used as an alternative to tissue‐derived stromal cells. Accumulating evidence suggests that α‐smooth muscle actin‐expressing myofibroblast‐like cells or vascular endothelial cells are capable of promoting the proliferation of BMs (Kitani et al, 2011; Takenouchi et al, 2022; Tanaka et al, 1993).…”
Section: Introductionmentioning
confidence: 99%